Gramáticas Pedagógicas para o ensino de PLE: uma reflexão a partir do objeto indireto - Chamorro, Rebeca Wiezel (2022)
This research aimed to analyze Portuguese as a Foreign Language (PFL) textbooks grammars, focusing on the teaching aspects of the indirect object (IO) construction in Brazilian Portuguese (BP). The research presented is an exploratory-inductive study, with a qualitative paradigm, documentary nature and descriptive methodological basis, based on the perspective of grammar and language learning argued by Batstone (1994) and Larsen-Freeman (2003). Four PFL’s grammars were analyzed with publications made between 2010 and 2020. This investigation was based on studies that define the categories of Teaching Materials (TOMLINSON 2013; BROWN, 1994, LUCAS, 2016) and a brief historical background on some methodological trends of foreign language teaching. Finally, we built a characterization of the pronominal constructions of IO in BP through portuguese grammars and descriptive linguistic studies (CUNHA; CINTRA, 2001; BECHARA, 2009; CASTILHO, 2010; BERLINCK, 1996; MORAIS; BERLINCK, 2006; 2007). For the organization and analysis of data, 3 categories were elaborated: CAT. A - Elements of organization of the textbooks; CAT. B – Category sort and methodology references from the textbooks. C - Teaching procedures based on IO grammar content. The purpose of the categories is to make a diagnosis of how teaching about IO has been done in grammar textbooks of PFL. The results of this analysis indicate that there are factors such as: the teaching material category, the methodology foundation adopted by the material, the grammar and language perspective, which directly influence the grammar approach in PFL grammar textbooks that need to be known by educators and students for a better use these teaching materials. The data also indicate that, when opting for the non-systematization of grammar, many materials end up resorting to traditional normative classifications of BP that are unable to explain all occurrences of the verbal complementation of IO (CANÇADO; AMARAL, 2016). We sought to collaborate with a broader understanding of the possibilities of grammar teaching in grammar textbooks of PFL, in addition to verify, through analysis, how the content is being approached in materials that seek to explicitly explain the grammar of BP for foreigners.